Cardiac device-related infective endocarditis in the Czech Republic: Prospective data from the ESC EORP EURO-ENDO registry - Látal, Jan; Pazderník, Michal; Holická, Mária; Pelouch, Radek; Widimský, Jiří; Pudich, Jiří; Vančata, Radek; Širanec, Michal; Blechová, Kamila; Butta, Tadeáš; Mikulcová, Markéta; Mikulica, Michal; et al. (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2022)
AIM: Understanding cardiac electronic device infective endocarditis epidemiology is essential for the management of this serious complication. Only monocentric and limited data have been published regarding patients in the Czech republic so far. The aim of this study was to describe the current profile, microbiology and clinical characteristics of this population. PATIENTS AND METHODS: National data from the prospective ESC-EORP EURO-ENDO registry were collected. 57 consecutive patients with a diagnosis of cardiac device-related infective endocarditis (CDRIE) from 11 Czech centres were included. RESULTS: Staphylococcus spp. was responsible for 43.9% of isolates, whereas Culture negative endocarditis was documented in 26.3% episodes. The most frequent complications under therapy were acute renal failure (17.5%), septic shock and heart failure (both 10.5%). Extraction of device was performed in 75.4% of all patients, and the 1-year mortality was 22.5%. CONCLUSIONS: The high proportion of culture-negative endocarditis is alarming and warrants further investigation. Cardiac device related infective endocarditis is a serious complication with a high 1-year mortality in a highly polymorbid spectrum of patients.
Keywords: Endocarditis; Česká republika; Registries; Defibrillators, Implantable; endokarditida; registrace; lidé; prospektivní studie; defibrilátory implantabilní; Prospective Studies; Czech Republic; bakteriální endokarditida; Endocarditis, Bacterial; Humans